2012
DOI: 10.1016/j.foodcont.2011.12.015
|View full text |Cite
|
Sign up to set email alerts
|

The sanitizing action of essential oil-based solutions against Salmonella enterica serotype Enteritidis S64 biofilm formation on AISI 304 stainless steel

Abstract: a b s t r a c tBacterial adhesion and biofilm formation by Salmonella enterica serovar Enteritidis is a serious concern in the food processing industry; organism persistence in biofilms represents a continual source of contamination. Due to unsuccessful disinfection processes and emerging resistance, conventional control methods are rapidly becoming ineffective, necessitating the development of new control strategies. The following study evaluated the anti-biofilm effect of disinfectant solutions formulated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 25 publications
0
56
0
5
Order By: Relevance
“…Recently, essential oils have been used to control bacterial biofilms (Budzyñska et al, 2011;Oliveira et al, 2010;Valeriano et al, 2012), but few studies have evaluated the action of cinnamon EO and cinnamaldehyde. The effects of these compounds against Listeria monocytogenes, Escherichia coli, Pseudomonas spp., and Staphylococcus spp.…”
mentioning
confidence: 99%
“…Recently, essential oils have been used to control bacterial biofilms (Budzyñska et al, 2011;Oliveira et al, 2010;Valeriano et al, 2012), but few studies have evaluated the action of cinnamon EO and cinnamaldehyde. The effects of these compounds against Listeria monocytogenes, Escherichia coli, Pseudomonas spp., and Staphylococcus spp.…”
mentioning
confidence: 99%
“…Plant essential oils have been used for thousands of years all over the world (Ozkan et al, 2010;Valeriano et al, 2012). A great many of reports have suggested that some of the essential oils are useful in food preservation (Bendimerad et al, 2005;Mimica-Dukic et al, 2004) and also exhibit pharmacological properties such as antibacterial (Lo Cantore et al, 2009), spasmolytic (Olivier et al, 2009), antioxidant (Güllüce et al, 2003) and anticancer activities (Ashour, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Winkelstroter et al [11] and Winkelstroter et al [12] evaluated the use of antimicrobial molecules known as bacteriocins and that researchers found a potential use of them to influence Listeria monocytogenes biofilm formation. Valeriano et al [13] evaluated the anti-biofilm effect of with essential oils (EOs) of peppermint (Mentha piperita) and lemongrass (Cymbopogon citratus) against biofilm formation by S. enterica serotype Enteritidis S64.…”
Section: Biochemistry and Molecular Biology Journal Issn 2471-8084mentioning
confidence: 99%